2019
DOI: 10.1158/1538-7445.am2019-ct074
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT074: Tumor mutational burden (TMB) as a biomarker of survival in metastatic non-small cell lung cancer (mNSCLC): Blood and tissue TMB analysis from MYSTIC, a Phase III study of first-line durvalumab ± tremelimumab vs chemotherapy.

Abstract: Background High TMB is predictive of PFS benefit with anti-PD-(L)1 ± anti-CTLA-4 therapy in mNSCLC. Preliminary results from MYSTIC (NCT02453282), an open-label, Phase III trial of first-line durvalumab (D; anti-PD-L1), ± tremelimumab (T; anti-CTLA-4), vs platinum-based chemotherapy (CT) in mNSCLC, indicate that blood TMB (bTMB, ≥16 mut/Mb; GuardantOMNI [Guardant Health]) from circulating tumor DNA (ctDNA) correlates positively with tissue (t) TMB (≥10 mut/Mb) (Spearman’s correlation coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 0 publications
2
39
0
2
Order By: Relevance
“…A second bTMB assay, using the 500-gene panel Guardant OMNI, was evaluated in an exploratory analysis of the randomized phase III MYSTIC trial. A bTMB ≥ 20 Mut/Mb was significantly associated with OS and PFS benefit with durvalumab ± tremelimumab compared with platinum-based chemotherapy, with the greatest magnitude of benefit observed for patients receiving dual immune checkpoint blockage (HR 0.49 and 0.72 for OS and HR 0.53 and 0.77 for PFS with durvalumab-tremelimumab and durvalumab alone, respectively) [62]. Once again, bTMB did not correlate with PD-L1 expression levels.…”
Section: Blood Sample Tmb and Pd-l1mentioning
confidence: 83%
“…A second bTMB assay, using the 500-gene panel Guardant OMNI, was evaluated in an exploratory analysis of the randomized phase III MYSTIC trial. A bTMB ≥ 20 Mut/Mb was significantly associated with OS and PFS benefit with durvalumab ± tremelimumab compared with platinum-based chemotherapy, with the greatest magnitude of benefit observed for patients receiving dual immune checkpoint blockage (HR 0.49 and 0.72 for OS and HR 0.53 and 0.77 for PFS with durvalumab-tremelimumab and durvalumab alone, respectively) [62]. Once again, bTMB did not correlate with PD-L1 expression levels.…”
Section: Blood Sample Tmb and Pd-l1mentioning
confidence: 83%
“…It is important to note that ultimately, this trial did not show any survival difference by TMB (11). A preplanned exploratory analysis from the MYSTIC trial showed an OS benefit in patients with PTMB > 16 mutations/Mbp in front-line combined anti-PD-L1 and anti-CTLA4 immunotherapy for advanced NSCLC (31). However, the Neptune trial, which prospectively assessed the role of PTMB in this same setting with the same treatment failed to show any predictive relevance of PTMB in the primary analysis (32).…”
Section: Correlations With Clinical Historymentioning
confidence: 75%
“…Therefore, subsequent studies focused on the dual blockade of CTLA-4 and PD-1/PD-L1 [46]. Recently, two randomized phase III trials (CheckMate 227 and MYSTIC) showed improved activity compared with platinum-based chemotherapy only in selected patients with high tumor mutation burden with ipilimumab-nivolumab [47], while tremelimumab-durvalumab [48] failed to demonstrate any benefit in unselected patients. Therefore, a new generation of anti-CTLA-4 antibodies must show higher anti-tumor activity in order to achieve better outcomes.…”
Section: Discussionmentioning
confidence: 99%